CISG as an applicable law to harmonize the choice of law rules in the international sale of goods disputes especially in arbitral tribunal’s proceedings - Ahokanto, Joanna (My University, 2019)
The growth of international trade and international disputes has increased the interest to apply CISG as applicable law. CISG came into force in 1988 to harmonize the trade disputes and to the parties’ neural access to their rights and obligations. When CISG came into force, it had great importance in international trade. However, the restrictions on its scope weakened CISG. These restrictions mainly concerned consumer action, which left contractual freedom between buyers and sellers under national law. As a result, CISG has not been able to complete its role as the applicable law. For the above reasons, this thesis examines the actual application of CISG in arbitration and, secondly, whether CISG could, in the future, overrules national law in the disputes. The main concentration is on arbitration since about 70% of cases are dealt with by arbitration, CISG has been the applicable law. This thesis tries to answer on if arbitral tribunals apply CISG as applicable law in the same matter or do tribunals face the question of applicable law differently in international and national tribunals. The purpose is to find out how CISG can be used as a choice of law in arbitration and whether the choice of law rules are consistent in arbitral tribunals. The thesis explains the background to the application of CISG in international and national arbitration tribunals, analyses the fulfilment of the CISG criteria and the choice of law in contracts where CISG is or has not been chosen to apply the law. The sources of the thesis consist primarily of the settlement practices of both international and national arbitrators. In analysing the fulfilment of CISG's competence criteria, I will also focus on the resolution made in national practice. Literature plays an essential role, especially in the analysis section of the thesis. In conclusion, in the light of recent developments in arbitration, CISG has emerged as a law applicable to the new rise. In particular, in international arbitration, CISG is used as a general guideline for the settlement of trade disputes. The case-law shows that in the future CISG's principles will be increasingly used in situations where the parties' agreement does not only concern trade in goods. However, based on my research, the arbitration practice of the arbitral tribunal remains opaque, and actual knowledge of the application of CISG remains superficial.
Keywords: International Law – International Commercial Law, CISG, Arbitration, Arbitral Tribunal, Choice Of Law, Jurisdiction, Dispute Resolution